2007
DOI: 10.12968/ijtr.2007.14.5.23538
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of therapy student's perceptions of cultural awareness

Abstract: Cultural awareness is recognized as an essential skill for the effective practice of physiotherapy and occupational therapy. The aim of this study was to investigate the perceptions of cultural awareness of 274undergraduate physiotherapy and occupational therapy students. A self administered questionnaire adapted and modified from Cheung et al (2002) was used. More than half of the students recognized the influence of cultural factors on the assessment and intervention process and the functional ability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 14 publications
0
11
0
2
Order By: Relevance
“…Research has indicated that occupational therapy practitioners acknowledge the need to understand and develop cultural awareness and competency as a part of education and clinical practice (Cheung et al, 2002;Kale & Hong, 2007;Mu et al, 2010;Munoz, 2007;Murden et al, 2008;Rasmussen et al, 2005;Whiteford & St-Clair, 2002). Research shows that cultural awareness and competency are an evolving and developing process, yet continues to be "one of the least developed aspects of occupational therapy" (Awaad, 2003, p.358;Black & Wells, 2007).…”
Section: Cultural Competency and Occupational Therapy Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has indicated that occupational therapy practitioners acknowledge the need to understand and develop cultural awareness and competency as a part of education and clinical practice (Cheung et al, 2002;Kale & Hong, 2007;Mu et al, 2010;Munoz, 2007;Murden et al, 2008;Rasmussen et al, 2005;Whiteford & St-Clair, 2002). Research shows that cultural awareness and competency are an evolving and developing process, yet continues to be "one of the least developed aspects of occupational therapy" (Awaad, 2003, p.358;Black & Wells, 2007).…”
Section: Cultural Competency and Occupational Therapy Educationmentioning
confidence: 99%
“…As the multicultural population of the United States increases, all health care providers must effectively interact with clients from culturally diverse settings (Masin, 2011). Cultural awareness and the development of cultural competency is vital to effective occupational therapy practice and providing services to these diverse populations (Kale & Hong, 2007;Mu, Coppard, Bracciano, Doll, & Matthews, 2010). Occupational therapy practitioners must be aware of and respond to cultural differences that influence clients' occupational performance, assessments, and intervention outcomes (Murden et al, 2008;Rasmussen, Lloyd, & Wielandt, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These differences provided the impetus to develop a new scale to assessing cultural awareness in Latin America, based on recently published theoretical data and empirical data collected from local practitioners (CASTRO; DAHLIN-IVANOFF; MÅRTENSSON, 2016a, b). The use of the two instruments in research also differs as since publication, the CASQ has been used in four related studies, whereas the ECCETO has not been used (CASTRO; DAHLIN-IVANOFF; MÅRTENSSON, 2016a;CHERRY et al, 2009;CHEUNG;SHAH;MUNCER, 2002;KALE;SWEE HONG, 2007;MURDEN et al, 2008;RASMUSSEN et al, 2005). Further investigation is required with larger groups of students to fully compare both instruments.…”
Section: Test-retest Reliability Evaluation Of the Escala De Conciencmentioning
confidence: 99%
“…Further exploration should also focus on the development of similar scales for practitioners and faculties, and in other regions outside English-speaking countries, where the currently available scale has been designed and implemented (CHERRY et al, 2009;CHEUNG;SHAH;MUNCER, 2002;KALE;SWEE HONG, 2007;MURDEN et al, 2008;RASMUSSEN et al, 2005). Socio-historical conditions and practice contexts for occupational therapists also need to be addressed when research is being designed (GUAJARDO; KRONENBERG; RAMUGONDO, 2015).…”
Section: Test-retest Reliability Evaluation Of the Escala De Conciencmentioning
confidence: 99%
See 1 more Smart Citation